2016
DOI: 10.1080/20786190.2016.1186367
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of blood pressure control and its determinants among patients with primary hypertension seen in a primary care setting in Western Nigeria

Abstract: Achieving guideline-recommended blood pressure is imperative in reducing the rising tide of uncontrolled hypertension and its attendant sequelae, which are major causes of morbidity and mortality globally. The aim of the study was to describe the pattern of blood pressure control and identify the factors influencing blood pressure control among patients with primary hypertension seen at family medicine clinics of FMC, Abeokuta. Methods: This was a descriptive cross-sectional hospital-based study. A systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…This observation agrees with previous reports highlighting the fact that in most countries, less than 20% of patients achieve BP goals and therapy with a single antihypertensive agent fails to achieve BP goals in up to 80% of patients [1] The prevalence of uncontrolled hypertension observed in the present study was similar than that reported by Dennison et al (64%) [26], Rayner et al (60.2%) [27].and by Abiodun et al .62.3%, (67%) [28]. It lower than that reported by Mutua [37] The differences in these studies can be justified by the media, the different sample sizes, the references retained as control (140/90 and BP.130 / 80 mmHg), and finally the co-morbidity in the presence (CKD and DM) and without forgetting the quality of the drugs which differs from country to country…”
Section: Discussionsupporting
confidence: 73%
“…This observation agrees with previous reports highlighting the fact that in most countries, less than 20% of patients achieve BP goals and therapy with a single antihypertensive agent fails to achieve BP goals in up to 80% of patients [1] The prevalence of uncontrolled hypertension observed in the present study was similar than that reported by Dennison et al (64%) [26], Rayner et al (60.2%) [27].and by Abiodun et al .62.3%, (67%) [28]. It lower than that reported by Mutua [37] The differences in these studies can be justified by the media, the different sample sizes, the references retained as control (140/90 and BP.130 / 80 mmHg), and finally the co-morbidity in the presence (CKD and DM) and without forgetting the quality of the drugs which differs from country to country…”
Section: Discussionsupporting
confidence: 73%
“…Comparative prevalence of B.P control in Africa revealed 50.3% in Ethiopia and 33.4% in Kenya [8,9]. In Nigeria, proportion of blood pressure control ranges from 17.2 -53.3% [10][11][12][13]. The current emphasis is on the control of both the systolic and diastolic blood pressure, the systolic hypertension is by far common in low socio-economic people as compared to diastolic hypertension [9].…”
Section: Introductionmentioning
confidence: 99%
“…The current emphasis is on the control of both the systolic and diastolic blood pressure, the systolic hypertension is by far common in low socio-economic people as compared to diastolic hypertension [9]. Between 2009 and 2010, only 50% of adult subjects with hypertension have their B.P controlled below 140/90mmHg [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations